The Applicability and Limitations of the Spectrofluorometric Method for Determination of ALDH1 Activity in Serum and Plasma - Sylwia Michorowska; Agnieszka Wiśniewska; Renata Wolinowska; Piotr Wroczyński; Joanna Giebułtowicz (Diagnostics)
Background: Aldehyde dehydrogenase class 1 (ALDH1) is an enzyme that is ubiquitously distributed in adult tissues and may serve as a prognostic marker in various cancer types. In blood, 99% of ALDH1 is found in erythrocytes; although, it was also demonstrated that leukocytes and platelets exhibit ALDH activity. No ALDH activity was detected in plasma, even when employing the highly sensitive fluorometric method with 7-methoxy-1-naphthaldehyde as a substrate. However, some reports have been released describing stable and measurable ALDH1 activity in the serum of healthy subjects using 6-methoxy-2-naphthaldehyde as a substrate and a Shimadzu RF—5301 spectrofluorometer. Methods: Our study aimed to verify whether ALDH1 activity can be measured in plasma or serum (n = 80) using 6-methoxy-2-naphthaldehyde as a substrate and a highly sensitive Hitachi F7000 spectrofluorometer, which offers a higher signal-to-noise ratio compared to the Shimadzu RF-5301. Additionally, HPLC with fluorometric detection was used to validate the results (n = 25) and analyze the influence of hemolysis (n = 5) and liver cell damage (n = 15) on ALDH1 activity in serum. Results: Measurable ALDH activity in serum/plasma was very rarely detected using a spectrofluorometer (2 cases out of 80). However, background drift in assays without coenzyme addition was observed, and it may be easily mistaken for ALDH or oxidase activity. Therefore, the spectrofluorometer drift observed in blank assays and modified by a matrix, e.g., enhanced in protein-rich samples, should be considered in ALDH1 activity assays. Conclusions: The spectrofluorometric method has limited applicability for determining ALDH activity in plasma and serum. HPLC can measure ALDH1 activity in plasma or serum; however, factors like hemolysis and elevated liver enzymes significantly affect activity and must be considered in diagnostic interpretations. To enhance research quality on ALDH1 as a biomarker for diseases, including cancers, we recommend using control samples, reference materials, and purifying commercially available aldehyde substrates to improve method sensitivity.